Nutrients and non-nutrients composition and bioactivity of wild and cultivated Coprinus comatus (O.F.Müll.) Pers. - Stojković, Dejan (2013)
Mushrooms have been reported as sources of biomolecules with various potential. Coprinus comatus was studied to obtain information about this species, comparing cultivated and wild samples. Free sugars, fatty acids, tocopherols, organic acids and phenolic acids were analysed by chromatographic techniques coupled to different detectors. C. comatus methanolic extractwas tested for its antioxidant potential (reducing power, radical scavenging activity and lipid peroxidation inhibition) and antimicrobial properties (tested towards Gram positive and negative bacteria, and microfungi). The toxicity for liver cells was tested in porcine liver primary cells. Both studied samples revealed similar nutritional value and energy contribution. The cultivated sample revealed the highest content in free sugars, monounsaturated fatty acids and tocopherols, while the wild mushroom was richer in saturated and polyunsaturated fatty acids, organic acids and phenolic compounds. The cultivated species also revealed the highest antioxidant potential and antimicrobial activity (with exception towards Gram negative bacteria and Aspergillus ochraceus). Both species revealed no toxicity towards porcine liver cells. The present study proved that cultivated and wild mushrooms from the same species could be excellent options as food and as sources of nutritional and bioactive compounds. Furthermore, differences in wild and cultivated samples were comparatively investigated for the first time.